2016
DOI: 10.1016/j.otsr.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Direct lateral vs posterolateral approach to hemiarthroplasty for femoral neck fractures

Abstract: Level 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 35 publications
2
35
0
2
Order By: Relevance
“…Yli-Kyyny et al (15 and personal communication from Yli-Kyyny) found the dislocation rate of the Lubinus sp II hemiendoprosthesis (cemented, modular, unipolar) to be 9.0% using the posterior approach and 3.0% using the Hardinge approach. Similarly, Mukka et al (19) found a dislocation rate of 8.4% with Lubinus sp II hemiendoprosthesis (cemented, modular, unipolar) when using the posterior approach. Kanto et al (9) reported a 6.8% dislocation rate following insertion of the Lubinus sp II hemiendoprosthesis (cemented, modular, unipolar) using the posterior approach.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Yli-Kyyny et al (15 and personal communication from Yli-Kyyny) found the dislocation rate of the Lubinus sp II hemiendoprosthesis (cemented, modular, unipolar) to be 9.0% using the posterior approach and 3.0% using the Hardinge approach. Similarly, Mukka et al (19) found a dislocation rate of 8.4% with Lubinus sp II hemiendoprosthesis (cemented, modular, unipolar) when using the posterior approach. Kanto et al (9) reported a 6.8% dislocation rate following insertion of the Lubinus sp II hemiendoprosthesis (cemented, modular, unipolar) using the posterior approach.…”
Section: Discussionmentioning
confidence: 87%
“…This may be due to the fragility of these patients and due to the fact that minor complications like superficial infections are treated in primary healthcare centers, with only major complications being referred to specialized care. The number of deep (prosthetic) infections was acceptable (13,15,19). However, it is possible that late infections are underestimated because the most fragile patients may have been determined unfit for reoperation by a general practitioner and treated with suppression antibiotics in the healthcare centers without orthopedic consultation.…”
Section: Discussionmentioning
confidence: 99%
“…In Paper I, patients operated with PA had better patient-reported outcomes after HA for FNF, when compared to DLA. (91). In a letter to the editor of Acta Orthopaedica, Rogmark (182) (Appendix III) questioned our conclusions on patient-reported outcomes based on the fact that the response rate of 50% in our study was rather low.…”
Section: Paper Imentioning
confidence: 80%
“…Rogmark and Leonardsson published a review of RCTs and register studies reporting an increased risk of dislocation with PA, and given the seriousness of dislocations they suggest that DLA is preferable (89). A recent review article by Fulham (2019) on DLA versus PA described observational studies (85,(90)(91)(92) recommending the DLA based on higher risk of posterior dislocation, but concluded that the evidence is limited and that the topic needs further investigation (93 probably less used due to its learning curve and surgeons' choice (106).…”
Section: Surgical Approachesmentioning
confidence: 99%
See 1 more Smart Citation